Combating Spring Frost With Ethylene - Liu, Jianyang; Sherif, Sherif M. (Frontiers in Plant Science, 2019)
The sustainable fruit production in temperate and boreal regions is often imperiled by spring frosts. The risk of frost damage and the resulting economic losses have recently been increasing as a result of the global climate change. Among the many approaches in mitigating frost damages, an ethylene-based compound, ethephon has proven to be effective in delaying bloom time in many fruit species and thereby avoid frost. However, effective concentrations of ethephon are often associated with harmful effects, which largely limit its use. Relatively limited research attention has been given to understand the mechanisms underlying this ethylene-mediated bloom delay, thus hindering the progress in exploring its potential in frost protection. Recent advances in omics and bioinformatics have facilitated the identification of critical molecular and biochemical pathways that govern the progression of bud dormancy in deciduous woody perennials. In this review, we summarized our current understanding of the function of ethylene and its interaction with other networks in modulating dormancy and blooming in temperate fruit trees. Some possible mechanisms are also proposed that might potentially guide future studies attempting to decipher the dormancy regulation or searching for methods to alleviate frost damages.